Clinical outcomes of COVID-19 and influenza in hospitalized children <5 years in the US - McGrath, Leah J.; Moran, Mary M.; Alfred, Tamuno; Reimbaeva, Maya; Di Fusco, Manuela; Khan, Farid; Welch, Verna L.; Malhotra, Deepa; Cane, Alejandro; Lopez, Santiago M. C. (Frontiers in Pediatrics, 2023)
We compared hospitalization outcomes of young children hospitalized with COVID-19 to those hospitalized with influenza in the United States. Methods: Patients aged 0-<5 years hospitalized with an admission diagnosis of acute COVID-19 (April 2021-March 2022) or influenza (April 2019-March 2020) were selected from the PINC AI Healthcare Database Special Release. Hospitalization outcomes included length of stay (LOS), intensive care unit (ICU) admission, oxygen supplementation, and mechanical ventilation (MV).Inverse probability of treatment weighting was used to adjust for confounders in logistic regression analyses.Results: Among children hospitalized with COVID-19 (n=4839; median age: 0 years), 21.3% had an ICU admission, 19.6% received oxygen supplementation, 7.9% received MV support, and 0.5% died. Among children hospitalized with influenza (n=4349; median age: 1 year), 17.4% were admitted to the ICU, 26.7% received oxygen supplementation, 7.6% received MV support, and 0.3% died. Compared to children hospitalized with influenza, those with COVID-19 were more likely to have an ICU admission (adjusted odds ratio [aOR]: 1.34; 95% confidence interval [CI]: 1.21-1.48). However, children with COVID-19 were less likely to receive oxygen supplementation (aOR: 0.71; 95% CI: 0.64-0.78), have a prolonged LOS (aOR: 0.81; 95% CI: 0.75-0.88), or a prolonged ICU stay (aOR: 0.56; 95% CI: 0.46-0.68). The likelihood of receiving MV was similar (aOR: 0.94; 95% CI: 0.81, 1.1).Hospitalized children with either SARS-CoV-2 or influenza had severe complications including ICU admission and oxygen supplementation. Nearly 10% received MV support. Both SARS-CoV-2 and influenza have the potential to cause severe illness in young children.